Strain-controlled fatigue and fracture of AISI 410 stainless steel. (December 2019) - Adinoyi, Muhammed J.; Merah, Nesar; Albinmousa, Jafar
Abstract: Microstructural characteristics, monotonic and strain-controlled cyclic axial behaviors of AISI 410 stainless steel were investigated. Grain size and distribution is uniform throughout the alloy's microstructure. Tensile behavior is characterized with high ductility yet mild strain hardening. Strain-controlled fatigue testing was conducted at strain amplitudes ranging from 0.3% to 0.9%. Cyclic stress softening was observed at all applied strain amplitudes. Hysteresis loops show that stress-strain stabilization was not reached by the alloy. Cyclic softening rate decreases with fatigue life and its ratio was independent of strain amplitude above 0.5%. An accumulating plastic damage behavior was exhibited by the alloy. Fatigue life data were well correlated with Coffin-Manson and plastic energy density damage equations. Multiple cracks were observed in specimens under monotonic and cyclic loadings. Highlights: Microstructural characterization in different orientations Cycle- and strain-dependent hysteresis loops evolution with fatigue cycles Study of softening behavior Fatigue life curves based on Coffin-Manson and plastic energy based analysis Post-fracture microscopic examination of crack and fracture surface